(untitled) - Chang, Raymond (Boston, MA, 2005)
Designed for the two-semester general chemistry course, Chang's textbook has often been considered a student favorite. This best-selling textbook takes a traditional approach. It features a straightforward, clear writing style and proven problem-solving strategies. The strength of the eighth edition is the integration of many tools that are designed to inspire both students and instructors. The textbook is the foundation for the technology. The multi-media package for the new edition stretches students beyond the confines of the traditional textbook.
Keywords: Chemistry